Athlete burnout: Is the type of sport a factor? - Holden, S. L.; Keshock, C. M.; Forester, B. E.; Pugh, S. F. (The Sport Journal, 2014)
Athletes sometimes become disenchanted with sport participation and stop competing at what might have been the pinnacle of their sport careers. Prior research has determined that athletes are likely to burnout if they are participating in sport for reasons other than sport attraction. However, prior research has not studied female athletes` comparative levels of burnout among various sports. The purpose of this study was to determine the level of burnout in female collegiate athletes based on their sport of choice. Participants were 108 female collegiate athletes at a Division I university in the Southeastern United States. Ages ranged from 19 to 24 (M= 19.8). Burnout was assessed by the Maslach Burnout Inventory (MBI). The instrument is divided into three subscales that include: Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment (PA). MBI scores on the subscales were used to classify participants as (1) low burnout (2) moderate burnout, or (3) high level of burnout. Results indicated female basketball athletes had the highest level of burnout in the areas of EE (M=27.2) and DP (M=8.5) which are classified as high (1) for EE and moderate (2) for DP. The volleyball players had the lowest sense of PA (M= 37.5) from their sport which correlates with a high (3) level of burnout. Participants on the track and field team experienced the lowest level of EE (M=12.7) which is classified as low burnout (1). Softball experienced the lowest level of DP (M=3.4) which is also classified as low (1), and tennis had the highest sense of PA (M=26.3) which means they were classified as having a low (1) level of burnout. Potential and current student athletes must be better educated in the area of stress and stress management. Further, they need to be better prepared for the demands of Division I collegiate athletics. Moreover, collegiate athletic departments should examine the programs offered to freshman athletes to include a course(s)/presentation(s) on stress and stress management to reduce the potential effects of burnout and avoid athletes quitting their sport. Finally, these efforts might be more intense in those sports where athletes indicated higher levels of burnout.